ORGANISASI NON-PROFIT (YAYASAN) SEBAGAI MEDIA TINDAK PIDANA PENCUCIAN UANG - Puanandini, Dewi Asri; Alamyah, Mohamad Fajar; Syabani, Aliefiyar Muchamad (CV Widina Media Utama, 2023)
Non-Profit Organizations such as Foundations receive attention when there are allegations of money laundering. In its development, the Foundation is used as a medium for money laundering due to the weak regulation of the organization of the Foundation. This research aims to find out how the legal arrangements of the Foundation, mapping risk factors and prevention efforts against the organization of the foundation as a medium for money laundering. This research is normative in nature using a statutory approach and conceptual approach. The results show that the Foundation is regulated through laws and government regulations, there are four risk factors for organizing foundations as a medium for money laundering, namely anonymous donations / mysterious donors, overvaluation of donated assets, misuse of funds, and other unusual transactions. Likewise, the importance of implementing proper due diligence procedures as an effort to prevent money laundering in the acceptance of foundation donations. The research concludes that money laundering threatens the integrity and stability of financial systems and institutions, including foundations. Foundation regulation in Indonesia is still limited, not comprehensive and very vulnerable to money laundering, so further research is needed to compare legislation in several other countries related to the Foundation.ABSTRAKOrganisasi Non-Profit seperti Yayasan mendapat perhatian ketika ada dugaan terjadinya pencucian uang. Dalam perkembangannya Yayasan dijadikan sebagai media pencucian uang akibat lemahnya pengaturan terhadap penyelenggaraan Yayasan. Penelitian ini bertujuan untuk mengetahui bagaimana pengaturan hukum Yayasan, memetakan faktor risiko dan upaya pencegahan terhadap penyelenggaraan yayasan sebagai media tindak pidana pencucian uang. Penelitian ini bersifat normatif menggunakan pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian menunjukkan bahwa Yayasan diatur melalui Undang-Undang dan peraturan pemerintah, terdapat empat faktor risiko penyelenggaraan yayasan sebagai media pencucian uang yaitu sumbangan anonim/donor misterius, overvaluation aset sumbangan, penyalahgunaan dana, dan transaksi tidak biasa lainnya. Demikian juga pentingnya penerapan due diligence procedure yang tepat sebagai upaya mencegah pencucian uang dalam penerimaan donasi yayasan. Kesimpulan penelitian bahwa pencucian uang mengancam integritas dan stabilitas sistem dan lembaga keuangan, termasuk yayasan. Pengaturan Yayasan di Indonesia masih terbatas, belum komprehensif dan sangat rentan terhadap pencucian uang, sehingga diperlukan penelitian lebih lanjut untuk membandingkan peraturan perundang-undangan di beberapa negara lain terkait Yayasan.